RNA Helicases in Microsatellite Repeat Expansion Disorders and Neurodegeneration - Castelli, Lydia M.; Benson, Bridget C.; Huang, Wan-Ping; Lin, Ya-Hui; Hautbergue, Guillaume M. (Frontiers in Genetics, 2022)
Short repeated sequences of 3-6 nucleotides are causing a growing number of over 50 microsatellite expansion disorders, which mainly present with neurodegenerative features. Although considered rare diseases in relation to the relatively low number of cases, these primarily adult-onset conditions, often debilitating and fatal in absence of a cure, collectively pose a large burden on healthcare systems in an ageing world population. The pathological mechanisms driving disease onset are complex implicating several non-exclusive mechanisms of neuronal injury linked to RNA and protein toxic gain- and loss- of functions. Adding to the complexity of pathogenesis, microsatellite repeat expansions are polymorphic and found in coding as well as in non-coding regions of genes. They form secondary and tertiary structures involving G-quadruplexes and atypical helices in repeated GC-rich sequences. Unwinding of these structures by RNA helicases plays multiple roles in the expression of genes including repeat-associated non-AUG (RAN) translation of polymeric-repeat proteins with aggregating and cytotoxic properties. Here, we will briefly review the pathogenic mechanisms mediated by microsatellite repeat expansions prior to focus on the RNA helicases eIF4A, DDX3x and DHX36 which act as modifiers of RAN translation in C9ORF72-linked amyotrophic lateral sclerosis/frontotemporal dementia (C9ORF72-ALS/FTD) and Fragile X-associated tremor/ataxia syndrome (FXTAS). We will further review the RNA helicases DDX5/17, DHX9, Dicer and UPF1 which play additional roles in the dysregulation of the RNA metabolism in repeat expansion disorders. In addition, we will contrast these with the roles of other RNA helicases such as DDX19/20, senataxin and others which have been associated with neurodegeneration independently of microsatellite repeat expansions. Finally, we will discuss the challenges and potential opportunities that are associated with the targeting of RNA helicases for the development of future therapeutic approaches.